2017
DOI: 10.1111/1462-2920.13931
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness of wildlife and livestock avian isolates of the nosocomial pathogen Acinetobacter baumannii to lineages spread in hospitals worldwide

Abstract: SummaryThe natural habitats and potential reservoirs of the nosocomial pathogen Acinetobacter baumannii are poorly defined. Here, we put forth and tested the hypothesis of avian reservoirs of A. baumannii. We screened tracheal and rectal swab samples from livestock (chicken, geese) and wild birds (white stork nestlings) and isolated A. baumannii from 3% of sampled chicken (n 5 220), 8% of geese (n 5 40) and 25% of white stork nestlings (n 5 661). Virulence of selected avian A. baumannii isolates was comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 65 publications
7
91
0
1
Order By: Relevance
“…Taking advantage of avian strain genome availability (32), we confirmed that the HU gene and the flanking regions are highly conserved with at least 99,1% identity between the avian strains' sequences and AB5075 strain sequence. Previously, five of these nine strains were found transformable in a qualitative transformation assay using the antibiotic-selection based method (32). All of the five strains were also found transformable using the fluorescencebased method but their ability to undergo transformation spreads over a range of three orders of magnitude ( Fig.…”
Section: Probing Natural Transformation In Non-clinical and Mdr Clinimentioning
confidence: 89%
See 4 more Smart Citations
“…Taking advantage of avian strain genome availability (32), we confirmed that the HU gene and the flanking regions are highly conserved with at least 99,1% identity between the avian strains' sequences and AB5075 strain sequence. Previously, five of these nine strains were found transformable in a qualitative transformation assay using the antibiotic-selection based method (32). All of the five strains were also found transformable using the fluorescencebased method but their ability to undergo transformation spreads over a range of three orders of magnitude ( Fig.…”
Section: Probing Natural Transformation In Non-clinical and Mdr Clinimentioning
confidence: 89%
“…Acinetobacter baumannii is now an established member of the growing list of bacteria capable of undergoing natural genetic transformation (13,32). Together with genomic evidence of high recombination rates and multiple horizontal gene transfer events, natural transformation should be considered as a major contributor of antibiotic resistance genes acquisition in A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations